2020
DOI: 10.31234/osf.io/qrbza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gambling on Others’ Health: Risky Pro-social Decision-Making in the Era of Covid19

Abstract: The current Covid-19 pandemic has demanded a degree of sacrifice from individuals for the sake of the greater good. Individuals have taken costly actions, both volitional and imposed, to reduce harm to strangers. The pandemic oers a unique opportunity to examine a fundamental question: where does the distinction between self and other lie? This question can be framed as a moral dilemma between competing motives of self-serving and pro-social behavior. Given the multifaceted uncer- tainty surrounding the Covid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Decisions in our study were risk-seeking, an effect which is in line with studies on different kinds of negative rewards, ranging from monetary loss ( [30]) to disease prevention ( [3]; [34]). In all these cases, participants became more riskaverse as the expected value of the negative event increased, an effect also confirmed in our study (Figure 3).…”
Section: Decisions For Others' Pain Are Less Riskysupporting
confidence: 80%
“…Decisions in our study were risk-seeking, an effect which is in line with studies on different kinds of negative rewards, ranging from monetary loss ( [30]) to disease prevention ( [3]; [34]). In all these cases, participants became more riskaverse as the expected value of the negative event increased, an effect also confirmed in our study (Figure 3).…”
Section: Decisions For Others' Pain Are Less Riskysupporting
confidence: 80%
“…Uncertainty has been extensively studied in economic decision-making ( [33]; [44]; [27];) particularly in the form of "risk", the uncertainty expected from available information. Previous studies have found that people avoid risk when facing gains, whereas they seek it when facing monetary loss ( [28]).…”
Section: Introductionmentioning
confidence: 99%